1968
DOI: 10.1136/bmj.3.5612.214
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Strokes Associated with Pregnancy and the Puerperium

Abstract: Summary: Thirty-one cases of ischaemic cerebral stroke occurring in association with childbirth were fully investigated. The Patients and Methods During the 10-year period 1956-65 a total of 523 patients were discharged fromn the neurosurgical unit at Killearn Hospital with the diagnosis of ischaemic carotid territory stroke. Twenty-three of the whole series were women who were pregnant or puerperal at the time of their stroke. During the same period 27 other pregnant or puerperal women were referred for inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 23 publications
1
67
0
1
Order By: Relevance
“…Arterial occlusion, other than venous thrombosis, has generally been accepted as a predominant cause of pregnancy-associated ischemic stroke, constituting ≈60% to 80% of cases in Western countries. For example, Cross et al 22 confirmed the incidence of ischemic stroke from venous origin to be 1 in 20 000 pregnancies in Scotland, and Wiebers et al 23 reported 1 patient in 26 000 deliveries at the Mayo Clinic. On the contrary, previous studies in Asian countries have demonstrated venous thrombosis as a more common cause of ischemic stroke than in Western countries.…”
Section: Ischemic Strokementioning
confidence: 93%
“…Arterial occlusion, other than venous thrombosis, has generally been accepted as a predominant cause of pregnancy-associated ischemic stroke, constituting ≈60% to 80% of cases in Western countries. For example, Cross et al 22 confirmed the incidence of ischemic stroke from venous origin to be 1 in 20 000 pregnancies in Scotland, and Wiebers et al 23 reported 1 patient in 26 000 deliveries at the Mayo Clinic. On the contrary, previous studies in Asian countries have demonstrated venous thrombosis as a more common cause of ischemic stroke than in Western countries.…”
Section: Ischemic Strokementioning
confidence: 93%
“…5 The incidence during pregnancy was reported to be 5 infarctions per 100 000 pregnancies in Glasgow, Scotland. 6 More recently, Sharshar et al 7 reported an incidence of 4.3 nonhemorrhagic strokes and 4.3 intracerebral hemorrhages per 100 000 deliveries. In the present study we report 69 strokes per 100 000 pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Bár egy korábbi tanulmány szerint az anyai halálozás 26% [32], újabb vizsgálatok 14% alatti mortalitást említenek [5]. A magzati halálozási arány körülbelül 12% [3].…”
Section: Prognózisunclassified